Nutritional support contributes to improving cardiac function and nutritional status in atrial fibrillation patients receiving treatment with esmolol hydrochloride - Liu, Xiaochao; Fan, Yulong; Liu, Zhi (Frontiers in Cardiovascular Medicine, 2025)
AimThis study focused on the effect of nutritional support combined with esmolol hydrochloride on the efficacy, nutritional status and quality of life of patients with atrial fibrillation (AF).MethodsThis retrospective cohort study categorised patients into a treatment group (TG) and a nursing group (NG) based on whether they received a high-quality care model, spanning the period from February 2021 to February 2024. Both groups received treatment with esmolol hydrochloride. The TG received standard care, while the NG received enhanced care (nutritional intervention + skin care) in addition to standard care. The study compared efficacy, cardiac function, nutritional status, adverse reactions, care satisfaction, and quality of life between the two groups.ResultEach group included 93 patients. The clinical efficacy of esmolol hydrochloride treatment in AF patients exceeds 90%, with nutritional care showing no significant enhancement of clinical outcomes (P = 0.249). However, compared to esmolol monotherapy, combined nutritional care intervention significantly reduced the length of hospitalisation, elevated Left ventricular ejection fraction (LVEF) levels, reduced Left ventricular systolic vector (LVESV) levels, and markedly improved nutritional indicators including Albumin (ALB), Total protein (TP), and Prognostic Nutritional Index (PNI). Furthermore, the combined intervention group demonstrated markedly improved nursing satisfaction and quality of life.ConclusionNutritional care administered alongside treatment with esmolol hydrochloride demonstrates superior efficacy in improving cardiac function, nutritional status, and quality of life among patients with AF.